Economics of crime deterrence and the rational offender - Eide, Erling; Aasness, Jørgen; Skjerpen, Terje (North-Holland, 1994)
In this volume, the rational choice model is extended to a framework of norm-guided theories of crime are incorporated. Based on this framework, a broad range of regression analyses of crime in various parts of the world is reviewed. Many general, methodological problems of empirical studies of crime are discussed, such as identification of models, model selection, measurement errors, and choice of measures corresponding to theoretical concepts. In an empirical chapter, using panel data for police districts in Norway, a novel procedure of identification of models of crime is employed. The model includes measurement relations allowing for random and systematic errors in the registered numbers of crimes and clear-ups. Academics in economics, criminology and sociology will find this book invaluable.
Keywords: Crime -- Economic aspects.; Crime -- Mathematical models.; elektronické knihy; electronic books